The Effect of Multi-Extrusion Process of Polylactic Acid on Tensile Strength and Fracture Morphology of Filament Product - Muhamad Syaifuddin; Heru Suryanto; Suprayitno Suprayitno (Universitas Negeri Malang, 2021)
Polylactic acid (PLA) is one of the most used materials in FDM 3D Printing. Large-scale consumption of PLA on an industrial scale could cause environmental and efficiency problems. Thus, PLA waste and industry waste need to be recycled to limit excessive waste. This study aimed to investigate the change in mechanical property, morphology, and structure of mechanically recycled PLA. Recycling was performed 12 times using the extrusion process with an extrusion temperature nozzle of 170°C. The SEM, structural analysis, and amorphous-crystalline analysis used XRD. The results showed a gradual decrease of tensile strength from each recycle with a total of 20% (13.22 MPa). The decrease percentage equalled the number of recycling. After the 9th recycle, PLA experienced a drastic tensile strength decrease, in which the 12th recycle tensile strength had a 14% (8.17 MPa) reduction. The morphology analysis of the tensile test sample presented significant morphology change, in which morphology defects such as void, flakes, and cracks appeared after the 6th recycle. Although, until 12 times extrusion, it did not significantly affect the PLA phase shape. Mechanical recycle using a multi-extrusion process is not recommended exceeding six times